Slurry improvement by vacuum preloading and electro-osmosis. Issue 2 (16th July 2018) - Li, Xiaobing; Zhao, Ran; Fu, Hongtao; Wang, Jun; Cai, Yuanqiang; Hu, Xiuqing; Zhou, Jie; Hai, Jun
Abstract : Vacuum preloading–electro-osmosis is one of the most useful ground improvement methods for soft soil but is not widely used in practical engineering because of its high power consumption and poor electro-osmotic efficiency in the later stages. To overcome these drawbacks, a new method – vacuum preloading with stepped-voltage electro-osmosis – is proposed in this paper. Five laboratory tests were performed on dredged slurry. The results showed that an appropriate stepped-voltage method is not only better than the general combined method but also requires less power and results in less electrode corrosion. For different initial voltages, the results indicated that an appropriate increase in the initial voltage significantly increased the water discharge; however, a higher initial voltage did not further improve the dredged slurry and led to increased energy consumption.